Identification of cardiovascular and molecular prognostic factors for the medium-term and long-term outcomes of sepsis (ICROS): protocol for a prospective monocentric cohort study. Issue 6 (23rd June 2020) - Coldewey, Sina M; Neu, Charles; Baumbach, Philipp; Scherag, Andre; Goebel, Björn; Ludewig, Katrin; Bloos, Frank; Bauer, Michael
Abstract : Introduction: Sepsis is one of the most prevalent life-threatening conditions in the intensive care unit. Patients suffer from impaired organ function, reduced physical functional capacity and decreased quality of life even after surviving sepsis. The identification of prognostic factors for the medium-term and long-term outcomes of this condition is necessary to develop personalised theragnostic approaches. Sepsis can cause cardiac impairment. The impact of this septic cardiomyopathy on patient's long-term outcome remains unclear. This study aims to evaluate cardiovascular risk factors, particularly the occurrence of septic cardiomyopathy, regarding their suitability as prognostic factors for the short-term and long-term outcomes of septic patients. Additionally, the study seeks to validate preclinical pathophysiological findings of septic cardiomyopathy in the clinical setting. Methods and analysis: In this prospective monocentric cohort study, patients will be clinically assessed during the acute and postacute phase of sepsis and two follow-ups after 6 and 12 months. To determine the effect of septic cardiomyopathy and concomitant cellular and molecular changes on patient mortality and morbidity, a comprehensive cardiovascular and molecular deep phenotyping of patients will be performed. This includes an echocardiographic and electrocardiographic assessment, and the evaluation of heart rate variability, body composition, mitochondrial oxygen metabolism, macrocirculation and microcirculation, and endothelial barrier function. These analyses are complemented by routine immunological, haematological and biochemical laboratory tests and analyses of the serum metabolome and lipidome, microbiome and epigenetic modifications of immune cells. The reversibility of patients' organ dysfunction, their quality of life and physical functional capacity will be investigated in the follow-ups. Patients with cardiomyopathy without infection and healthy subjects will serve as control groups. Ethics and dissemination: Approval was obtained from the Ethics Committee of the Friedrich Schiller University Jena (5276-09/17). The results will be published in peer-reviewed journals and presented at appropriate conferences. Trial registration numbers: DRKS00013347; NCT03620409 .